Zircon U–Pb evidence for the extent of the Meguma terrane and late Ediacaran magmatism in offshore Nova Scotia, Canada - Germain, Rémi; Kuiper, Yvette D.; White, Shawna E.; Crowley, James L. (Atlantic Geoscience, 2025)
A U–Pb LA-ICP-MS zircon study was conducted on 22 rock samples from offshore southeastern Nova Scotia, Canada, to investigate the nature of the pre-Mesozoic basement and the provenance of the overlying syn-rift Late Triassic Eurydice Formation of the Scotian Basin. Detrital zircon signatures from five offshore basement metasedimentary samples were consistent with those of the Meguma terrane. Three granitoid samples yielded ca. 381–358 Ma crystallization ages, consistent with felsic plutons of the onshore Meguma terrane. These results confirm that the Meguma terrane underlies the Scotian Basin. An isotopically evolved granodiorite yielded a ca. 576 Ma crystallization age and is interpreted as basement to the Meguma terrane. Its temporal, isotopic, and geochemical similarities with igneous rocks of the Ouarzazate Group in the Anti-Atlas of Morocco suggest that the Meguma terrane likely initiated in a Cadomian back-arc basin of northwest Africa. Detrital zircon signatures from the Eurydice Formation suggest that the late Ediacaran–Ordovician Meguma Supergroup was its primary sediment source, and absence of Silurian to Devonian zircon ages suggests that the rift-related Rockville Notch Group of the northwestern part of the Meguma terrane was not a source and likely absent below the Scotian Basin. The Rockville Notch Group was previously interpreted to represent rifting between Gondwana and the Meguma terrane. We interpret the ca. 576 Ma granodiorite as representing rifting between Gondwana and the Meguma terrane, and the Rockville Notch Group as Silurian rifting of an outboard Cadomian arc from the Meguma terrane.